The Influence of Economic Incentives, Helping the Company, and Platform Assistance on Tourist Visiting Decision to Jakabaring Sport City - R.A Ranti Maharani; Heri Setiawan (International Journal of Advanced Research in Social Studies, 2022)
This research aims to find out the effect of economic incentives, helping the company, and platform assistance on the decision to visit Jakabaring Sport City. The participants in this research were one hundred visitors of Jakabaring Sport City. A qualitative-descriptive approach with a questionnaire as the data collection technique was used. Multiple linear regression analysis was then applied to analyze the data. The results showed that economic incentives had a negative effect on the tourist visiting decisions while helping the company and the assistance platform had a positive and significant effect.